On the computation of option prices and Greeks under the CEV Model - Larguinho, M.; Dias, J. C.; Braumann, C. A. (Quantitative Finance, 2013)
Pricing options and evaluating Greeks under the constant elasticity of variance (CEV) model requires the computation of the non-central chi-square distribution function. In this article, we compare the performance, in terms of accuracy and computational time, of alternative methods for computing such probability distributions against an externally tested benchmark. In addition, we present closed-form solutions for computing Greek measures under the unrestricted CEV option pricing model, thus being able to accommodate direct leverage effects as well as inverse leverage effects that are frequently observed in options markets.